Dampak Pandemi Covid-19 pada Kualitas Laporan Keuangan Indonesia - Media Kusumawardani; Sri Maryati; Fardinant Adhitama; Achmad Soediro; Muhammad Farhan (Politeknik Ganesha Medan, 2022)
This study wants to examine the impact of COVID-19 on the quality of financial reports in Indonesia. The independent variable in this study is covid19, while the dependent variable is the quality of financial statements. The research sample consists of 432 manufacturing companies listed on the Indonesia Stock Exchange that report regularly from 2018 to 2020. The data collection method uses a purposive sample and this study uses secondary data. The study was tested using the SPSS program. The results of the study show that COVID-19 has a negative effect on the quality of financial reports. This study also shows that there is a difference between the quality of financial reports before Covid-19 and the quality of financial reports after Covid-19. The quality of financial reports (2018) has a difference to the quality of financial reports (2020). The quality of financial reports (2019) has a difference in the quality of financial reports (2020). In addition, based on descriptive data, the average quality of financial reports in the sample has decreased during covid19.